Analysis of the Influence of the Announcement of Stock Splits on Insider Trading Indicators in the Indonesian Stock Exchange Environment for the 2013-2023 Period - Rafie Thaqif Altamis Sormin (Syntax Idea)
The phenomenon of stock split is a corporate action to increase the number of shares outstanding in the market with the aim of making the stock price more affordable for investors. This practice is often carried out by company management to enhance stock liquidity and attract investor interest without necessarily increasing net income. However, although Stock Splits are generally considered a positive policy, some studies indicate that in some cases, Stock Splits can be exploited for insider trading activities, especially in markets with weak regulations or emerging markets. The aim of this research is to find out whether there are indicators of insider trading from stock split policies based on similar behavior in capital markets where capital market regulations are still not well regulated ( emerging markets ). By using the event study method, this research did not find any indication of insider trading because there was no cumulative abnormal return in the positive direction before the stock split was executed. By using multiple regression analysis, this research confirms that there is no indication of insider trading which is influenced by the level of state ownership, small company asset size and the tendency to split shares with a high split ratio as has been tested by previous research.